2012
DOI: 10.1504/ijbex.2012.047908
|View full text |Cite
|
Sign up to set email alerts
|

Properties of quality constructs in Canadian business relationships

Abstract: This paper investigates whether satisfaction, in B2B relationships, is a mediating construct between the antecedents, trust and commitment, and subsequent outcomes. Using data from a survey of Canadian managers and executives, the study tested a structural equation model, the trust, commitment, satisfaction (TCS) model, where the antecedent constructs, trust and commitment, are mediated by the satisfaction construct, which in turn influences coordination, cooperation and continuity or 'consequence' constructs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
3
7
0
Order By: Relevance
“…The importance of trust and commitment in manufacturersupplier relationships has been established in previous research across countries and company sizes (Lee et al, 2010;Svensson et al, 2010;Hutchinson et al, 2012;Mpinganjira et al, 2013;Rindell et al, 2013;Mysen et al, 2013). This study furthers our understanding of the positive effects of the assessed aspects on the economic satisfaction related to its non-economic (i.e.…”
Section: Concluding Thoughts and Suggestions For Future Researchsupporting
confidence: 66%
See 1 more Smart Citation
“…The importance of trust and commitment in manufacturersupplier relationships has been established in previous research across countries and company sizes (Lee et al, 2010;Svensson et al, 2010;Hutchinson et al, 2012;Mpinganjira et al, 2013;Rindell et al, 2013;Mysen et al, 2013). This study furthers our understanding of the positive effects of the assessed aspects on the economic satisfaction related to its non-economic (i.e.…”
Section: Concluding Thoughts and Suggestions For Future Researchsupporting
confidence: 66%
“…Several studies support the notion that the constructs of trust, commitment and satisfaction are important for establishing and maintaining successful and enduring business relationships (Palmatier et al, 2006;Lee et al, 2010;Svensson et al, 2010;Hutchinson et al, 2012;Mpinganjira et al, 2013;Rindell et al, 2013;Mysen et al, 2013). They are therefore considered as important constructs in the development and establishment of relationship quality in business relationships (Ulaga and Eggert, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Satisfaction is widely considered as a guiding philosophy of business relationships (Yeung et al , 2013). Empirically, its importance is evidenced by the many studies that have found satisfaction to be an important factor for the success of business relationships (Del Bosque Rodríguez et al , 2006; Hutchinson et al , 2012; Human and Naudé, 2014; Hashim and Tan, 2015). Reviews of literature on studies that have focused on the quality of business relationships, especially in the context of direct and indirect channel relationships, show that satisfaction is closely related to trust and commitment (Voldnes et al , 2012; Mpinganjira et al , 2014), with Walter et al (2003) and Sarmento et al (2014) describing the three constructs as key indicators of relationship quality.…”
Section: Introductionmentioning
confidence: 99%
“…However, similar to previous studies (e.g. see Hutchinson et al, 2012;Mpinganjira et al, 2013;Mysen et al, 2015;Pad ın et al, 2017), we build on existing literature showing a positive relationship between trust and commitment (e.g. Mungra and Yadav, 2019;Pad ın et al, 2017;Razzaque and Boon, 2003) by hypothesizing that satisfaction mediates between these two antecedent constructs (top half of the model) and the postcedents coordination, continuity and cooperation (bottom half of the model).…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 74%